Comparison of the Profile and TSH Levels from Several Types of Blood Collection Tubes - Putra, Gunawan Eka; Sukartini, Ninik; Immanuel, Suzanna; Henrika, Fify; Indrasari, Nuri Dyah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Thyroid-Stimulating Hormone (TSH) is an important parameter in diagnosing thyroid disease which uses serumaccording to the World Health Organization's (WHO) recommendations. The use of plasma can help improve the TurnAround Time (TAT); however, the discrepancy with serum is unknown. A cross-sectional study using 89 blood samples wasperformed to compare TSH levels using serum tubes with clot activator (Tube I), plasma tubes with heparin (Tube II), andplasma tubes with heparin-gel separator (Tube III); and to overview of TSH levels according to gender and age. The medianof TSH levels in Tubes I, II, and III were 1.380 (0.032-7.420) μIU/mL, 1.380 (0.030-7.480) μIU/mL, and 1.360 (0.030-7.460)μIU/mL, respectively. There were no statistically significant differences in TSH levels of the three tubes. The median TSHlevels differences of Tubes II and III compared to the tube I were -0.9% (-7.2-2.2) and -1.7% (-8.0-1.6), respectively.Measurement bias observed in this study was following the specified desirable bias according to Ricos. The median TSHlevels of the male and female groups were 1.500 (0.032-4.250) μIU/mL and 1.345 (0.058-7.420) μIU/mL, respectively. MedianTSH levels of 31-40 years old age group and >61 years old age group were 1.190 (0.609-3.240) μIU/mL and 1.730 (0.088-5.760) μIU/mL, respectively. Specimens from three tubes could be used to examine TSH levels. Measurement of TSH levelsshowed a higher median in the male and older group.